Antioxidant Activity and Cytotoxicity of Taraxacum hispanicum Aqueous and Ethanolic Extracts on HepG2 Cells - Laranjeira, C. (2021)
Plants belonging to the genus Taraxacum have been used in traditional medicine. Nowadays, extracts of these plants have been reported for the treatment of diseases, including liver disorders. Increasing interest and research on these plants also revealed its potential for treating cancer. This study aims to evaluate the antioxidant activity and cytotoxic properties of crude extracts from aerial parts of Taraxacum hispanicum H.Lindb, against human hepatocarcinoma (HepG2). Material and methods: Evaluation of the antioxidant properties was performed using DPPH in vitro test, superoxide scavenging assay and Fe2+ chelating activity. MTT assay was used to determine metabolic activity, for 24 and 48 hours.